Milton, Mill, and Berlin's History of Monism and Pluralism. Issue 4 (1st October 2020) - Lobis, Seth
ABSTRACT: Isaiah Berlin makes two brief references to John Milton in the essay he strategically titled "John Stuart Mill and the Ends of Life." The references establish a contrast between Milton and Mill by associating Milton with moral monism and Mill with its opposite, value pluralism. Yet a careful reading of Milton's Areopagitica, cited dismissively in the essay, reveals the inadequacy of Berlin's intellectual-historical account of the two concepts, which he presents as fully distinct and diametrically opposed. Although still heuristically valuable, Berlin's account warrants historiographic revision and refinement, as his treatments of both Milton and Mill make apparent.